Implementasi Logistic Regression dalam Sistem Diagnosa Penyakit Diabetes dengan KNN - Wahyudi, I Wayan Trisna; Kadyanan, I Gusti Agung Gede Arya (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
Diabetes is a serious chronic disease that occurs when the pancreas does not produce enough insulin. The number of Indonesians suffering from diabetes is estimated to reach 8.2 million in 2020. The existing method for the detection of diabetes is to use laboratory tests. Logistic regression is a statistical tool that can be used in classification modeling about the presence or absence of diabetes. The aim of this study is to predict diagnostically whether a patient has diabetes or not. The results obtained are relatively low predictions because the ranges of values of several factors that cause it are very far apart so normalization is carried out so that the ranges of values are close together. A system can be developed to predict the disease using the principle of classification.